The effects of surgeon handedness on the efficacy and safety of proximal femoral nail antirotation fixation for intertrochanteric femur fractures in elderly patients: A single Center’s experience - Liu, Xiao-Feng; Zheng, Yong-Qiang; Lin, Liang; Lin, Zhen-Yu; Zhang, Hong-Peng; Huang, Xiao-Peng; Wang, Ze-Feng; Fang, Yang-Zhen; Zhang, Wen-Ming; Fang, Xin-Yu; Zhang, Jin-Shan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundHandedness refers to the lateral preference of using one hand more than the other. Surgeon handedness has been widely discussed in operative surgery and could cause clinical discrepancy. However, in the use of proximal femoral nail antirotation (PFNA) for the treatment of intertrochanteric femur fracture (IFF), the effect of handedness on clinical outcomes is easily overlooked. In fact, when right-handed surgeons operate on right-sided IFF patients, due to the specific nature of the surgical site, they have to use their left hand to perform the opening at the proximal end of the femur and insert the main nail. This study aimed to investigate the influence of surgeon handedness on the efficacy and safety of PFNA fixation for elderly patients with IFF.MethodsA retrospective analysis was conducted on the basic data of 182 elderly patients with IFF who underwent surgical treatment in our department from January 2020 to December 2022 and had a minimum follow-up duration of 1 year. Equal numbers of left and right PFNA fixation were performed by four surgeons, two right-handed and two left-handed. Dominant group refers to a left IFF for a right-handed surgeon and a right IFF for a left-handed surgeon. Otherwise, it is called a non-dominant group. The patients were divided into the dominant group (90 cases) and the non-dominant group (92 cases), and differences between the two groups were analyzed.ResultsIn terms of surgical safety, the dominant group had significantly shorter average operation time and lower blood loss compared to the non-dominant group (P < 0.05). In the final follow-up, the average Harris score of the dominant group was 84.60 ± 4.35, and that of the non-dominant group was 82.63 ± 4.98. The Harris score of the dominant group was significantly higher than that of the non-dominant group (P < 0.05). According to the 1-year follow-up results, there were 86 survivors and 4 deaths in the dominant group, and 80 survivors and 12 deaths in the non-dominant group. Although the non-dominant group (13.04%) had a higher mortality rate than the dominant group (4.44%), the difference between the two groups was not statistically significant (P > 0.05).ConclusionSurgeon handedness is a factor that influences the efficacy and safety of PFNA fixation for patients with IFF.